Economics of Tuition Fees: Cost-Benefit Analysis of a Differentiated Tuition Fee System in Selected Ugandan Universities - Muhanguzi, Kibs; Sumil, Novembrieta; Kibuuka, Muhammad; Mwebesa, Edson; Katushabe, Scovia; Sumil, Manuel; Nakimuli, Amina (Bugema International Multi-Disciplinary Conference, 2015)
The post millennium development (sustainable development) goals are a long term strategic plan by the United Nations’ member governments meant to ensure improved human development. Human development, the main sustainable development goal can emanate from product differentiation. Access to education is a sustainable development strategy that can improve quality of life. A differentiated tuition fee system is thought to be one of the approaches to improve people’s quality of life. Anchored on the monopolistic price discrimination theory (third degree), this paper examined the costs and benefits derived from a differentiated tuition fee system in selected Ugandan universities. To achieve this, a descriptive correlation approach and mixed explanatory designs (quantitative and qualitative) were adopted. The study found tuition fee differentiation system to have a significant correlation with benefits accrued and an insignificant correlation with costs involved.
Keywords: Cost-benefit analysis; Differentiated tuition fee system; Economics of tuition fees